Thermodynamic properties of mansfieldite (AlAsO4·2H2O), angelellite (Fe4(AsO4)2O3) and kamarizaite (Fe3(AsO4)2(OH)3·3H2O). (15th May 2018) - Majzlan, Juraj; Nielsen, Ulla Gro; Dachs, Edgar; Benisek, Artur; Drahota, Petr; Kolitsch, Uwe; Herrmann, Julia; Bolanz, Ralph; Števko, Martin
ABSTRACT: Thermodynamic data for the arsenates of various metals are necessary to calculate their solubilities and to evaluate their potential as arsenic storage media. If some of the less common arsenate minerals have been shown to be less soluble than the currently used options for arsenic disposal (especially scorodite and arsenical iron oxides), they should be further investigated as promising storage media. Furthermore, the health risk associated with arsenic minerals is a function of their solubility and bioavailability, not merely their presence. For all these purposes, solubilities of such minerals need to be known. In this work, a complete set of thermodynamic data has been determined for mansfieldite, AlAsO4 ·2H2 O; angelellite, Fe4 (AsO4 )2 O3 ; and kamarizaite, Fe3 (AsO4 )2 (OH)3 ·3H2 O, using a combination of high-temperature oxide-melt calorimetry, relaxation calorimetry, solubility measurements, and estimates where possible and appropriate. Several choices for the reference compounds for As for the high-temperature oxide-melt calorimetry were assessed. Scorodite was selected as the best one. The calculated Gibbs free energy of formation (all data in kJ·mol –1 ) is –1733.4 ± 3.5 for mansfieldite, –2319.2 ± 7.9 for angelellite and –3056.8 ± 8.5 for kamarizaite. The solubility products for the dissolution reactions are –21.4 ± 0.5 for mansfieldite, –43.4 ± 1.5 for angelellite and –50.8 ± 1.6 for kamarizaite. Available, but limited, chemical data for the natural scorodite–mansfieldite solid-solution series hint at a miscibility gap; hence the non-ideal nature of the series. However, no mixing parameters were derived because more data are needed. The solubility of mansfieldite is several orders of magnitude higher than that of scorodite. The solubility of kamarizaite, on the other hand, is comparable to that of scorodite, and kamarizaite even has a small stability field in a pH-pε diagram. It is predicted to form under mildly acidic conditions in acid drainage systems that are not subject to rapid neutralization and sudden strong supersaturation. The solubility of angelellite is high, and the mineral is obviously restricted to unusual environments, such as fumaroles. Its crystallization may be enhanced via its epitaxial relationship with the much more common hematite. The use of the scorodite–mansfieldite solid solution for arsenic disposal, whether the solid solution is ideal or not, is not practical. The difference in solubility products of the two end-members (scorodite and mansfieldite) is so large that almost any system will drive the precipitation of essentially pure scorodite, leaving the aluminium in the aqueous phase.